2023
DOI: 10.3390/nano13081407
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Nanostructured Cemented Carbides with Alternative FeNi and FeNiCo Binders

Abstract: Nanostructured cemented carbides with Co binders have shown excellent mechanical properties in various applications. Nevertheless, their corrosion resistance has shown to be insufficient in different corrosive environments, leading to premature tool failure. In this study, WC-based cemented carbide samples with different binders were produced using 9 wt% of FeNi or FeNiCo with the addition of Cr3C2 and NbC as the grain growth inhibitors. The samples were investigated using electrochemical corrosion techniques:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is also possible to notice that the slope of the curve is much milder in the case of the heat-untreated sample, and that all four curves were shifted in a negative direction, which indicates the corrosion instability of the working electrodes in the chloride medium. All samples showed the same trend and good repeatability of the results [45,46].…”
Section: Electrochemical DC Measurementsmentioning
confidence: 61%
See 2 more Smart Citations
“…It is also possible to notice that the slope of the curve is much milder in the case of the heat-untreated sample, and that all four curves were shifted in a negative direction, which indicates the corrosion instability of the working electrodes in the chloride medium. All samples showed the same trend and good repeatability of the results [45,46].…”
Section: Electrochemical DC Measurementsmentioning
confidence: 61%
“…It is also possible to notice that the slope of the curve is much milder in the case of the heat-untreated sample, and that all four curves were shifted in a negative direction, which indicates the corrosion instability of the working electrodes in the chloride medium. All samples showed the same trend and good repeatability of the results [45,46]. From the numerical and graphical values of Ecorr (Table 5 and Figure 11), it can be concluded that nitriding time has no significant influence on the corrosion stability of the samples of nitrided AISI 316L steel in the test medium.…”
Section: Electrochemical DC Measurementsmentioning
confidence: 62%
See 1 more Smart Citation
“…To characterize the corrosion behavior and to determine coating protective properties, open circuit potential (OCP) and electrochemical impedance spectroscopy (EIS) analyses were conducted [39] with a VersaSTAT 3 Potentiostat/Galvanostat (AMETEK Scientific 131 Instruments, Princeton applied research, Berwyn, PA, USA). The measurements were performed in 3.5% NaCl solution, and the results were obtained after 24, 250, and 500 h of immersion at room temperature (23 ± 2) • C. This is a standard test solution, used in many papers because it simulates the marine environments since it is the average concentration of salt in the oceans [40][41][42]. The frequency range of the EIS test was 10 5 -10 −1 Hz with 100 mV amplitude operating at ten points per decade.…”
Section: Methodsmentioning
confidence: 99%
“…In the beginning, Ching's primers' samples displayed an incomplete semicircle, indicating a robust coating. At this time, the electrolyte had not yet damaged the coating's substrate, so the coating provided high resistance which the current could not penetrate [41]. Hempel's primer displayed a full semicircle after 1 day in the electrolyte, meaning the current was able to pass through, due to lack of coating's resistance.…”
Section: Chingmentioning
confidence: 99%